The Role of Agriculture and Agro-industries for Accelerating Economic Transformation in Egypt - El-Enbaby, Hoda (2017)
As part of 2016 IFPRI Egypt Seminar that was held in partnership with FAO on "Agriculture & Economic Transformation in MENA"